Technical Performance Analysis of Greco Roman and Freestyle Categories in Wrestling - Dedi Supriadi (STKIP Muhammadiyah Kuningan, 2022)
The purpose of this research is to analyze the techniques often used in Grecco Roman and Freestyle wrestling matches in the 2019 Word Championship international match event held in Kazakhstan. The method in this study used a non-experimental descriptive design. Data collection used video analysis of the performance of four athletes at the time of the event. The results showed that: 1) An athlete named Tamas Lorincz in the 77 kg greco roman style category performed waist roll, push, kayang and susupan techniques by 16.7%; 2) An athlete named Fumita Kenichiro in the greco roman style category of the 60 kg class performed the technique of waist slamming, force, and dance da suey by 33.3%; 3) An athlete named Uguev Zabur in the 57 kg freestyle category performed a push, take up, nelson technique of 17.6%; 4) An athlete named Hasan Yazdanichara in the 86 kg freestyle category performed a 37.5% foot roll, screw and nelson technique. From the results of these data it can be concluded that each athlete shows certain techniques related to performance, the results of this study can be a recommendation of coaches in providing technical exercises for the preparation of large competitions.